Novel Solution of Notch/All-pass Filter with Special Electronic Adjusting of Attenuation in the Stop Band - Sotner, R.; Jerabek, J.; Sevcik, B.; Dostal, T.; Vrba, K. (Elektronika ir Elektrotechnika, 2011)
The notch/all-pass filter with two electronically adjustable three-port current conveyors of the second generation (CCIIs) or oneconveyor and one voltage buffer employing only four passive elements is presented in this paper. Used active elements allow the controlof current transfer via DC control voltage. Therefore an adjusting of the attenuation in the stop band of the notch filter is possible. Thetransfer function and major parasitic influences of real active parts are discussed. The verification includes PSpice simulation withprofessional macromodels and measurement with available current conveyors in frequency domain. Ill. 7, bibl. 40 (in English; abstractsin English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.609